Utilization of Social Media Instagram the Gade Coffee and Gold Samarinda as an Online Marketing Communication - Hijrah, Lailatul; Andreana, Angelika Gita; Utami, Rezki Aguswidya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Currently, the field of entrepreneurship is proliferating, which results in increasing fierce business competition. A business aims to provide products and services to consumers and must strengthen personal branding so that the managed business can be well received in the community. In the era of digitalization, social media has developed as a tool used as a powerful weapon to interact with consumers, either as a means of communication, promotion, or buying and selling media. For this reason, this study aims to find out how the role and use of Instagram social media as a communication and online marketing tool at one of the cafes, namely The Gade Coffee and Gold Samarinda. The method used is a case study as part of qualitative research with data collection techniques in interviews. The results obtained are that the use of Instagram social media used by The Gade Coffee and Gold Samarinda can show an increase in sales. It means that Instagram as a social media can become a means of online marketing communication to reach more consumers.